2008
DOI: 10.1002/ijc.23808
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evaluation of epidermal fatty acid‐binding protein and calcyphosine, two proteins implicated in endometrial cancer using a proteomic approach

Abstract: With the aim to translate the discovery from proteomic research into clinical applications, we identified epidermal fatty acid-binding protein (E-FABP) and calcyphosine (CAPS) by MALDI-Q-TOF MS and validated their overexpressions by immunoblotting. Their expression statuses were examined by immunohistochemistry in 39 normal endometrium, 29 endometrial intraepithelial neoplasia (EIN) and 84 endometrial cancer (EC) cases. We evaluated the correlations to the clinicopathologic characteristics and determined wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…Survival analysis has indicated that CAPS is a potential survival predictor in breast cancer patients receiving adjuvant tamoxifen (25). Previous studies also revealed that CAPS was an independent prognostic factor for endometrial cancer patients (15,24) and colorectal cancer patients (17 (Fig. 3).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Survival analysis has indicated that CAPS is a potential survival predictor in breast cancer patients receiving adjuvant tamoxifen (25). Previous studies also revealed that CAPS was an independent prognostic factor for endometrial cancer patients (15,24) and colorectal cancer patients (17 (Fig. 3).…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, substantial attention has been been paid to the identification of biomarker targets, such as p53 (22) and heat shock protein 70 (23). A previous study showed that CAPS overexpression was significantly associated with histological grade in endometrial cancer (24). Another study demonstrated that CAPS could be a novel diagnostic biomarker for patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction of sequencing technology have aided in the discovery of new RNA molecules while providing more detailed understanding of biological pathways related to endometrial tumorigenesis [10]. Compared with traditional microarrays, which can only detect a limited number of miRNA, NGS enables in-depth characterization of the global range of miRNAs [10,11]. Also, it is suggested that genomic analysis of cells collected during Pap smears holds promise for early detection of EC [4,10].…”
Section: Next-generation Sequencing (Ngs)mentioning
confidence: 99%
“…In several papers, proteomics has been used to assess the clinical utility of biomarkers to evaluate their diagnostic and prognostic sensitivity and specificity by comparing protein profiles between pathological and normal tissue. It is belived that proteins are directly linked to the phenotype and the malignant nature of cancer, which explain the increased interest for studying global protein expression [11]. A study performed by Li et al exemplifies the value of proteomics where three potential EC-associated proteins were identified; Cyclophilin A (CypA), epidermal fatty acid-binding protein (E-FABP), and caclyphosine (CAPS) [11].…”
Section: Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation